2022
DOI: 10.7554/elife.76622
|View full text |Cite
|
Sign up to set email alerts
|

Full spectrum flow cytometry reveals mesenchymal heterogeneity in first trimester placentae and phenotypic convergence in culture, providing insight into the origins of placental mesenchymal stromal cells

Abstract: Single-cell technologies (RNA-sequencing, flow cytometry) are critical tools to reveal how cell heterogeneity impacts developmental pathways. The placenta is a fetal exchange organ, containing a heterogeneous mix of mesenchymal cells (fibroblasts, myofibroblasts, perivascular, and progenitor cells) . Placental mesenchymal stromal cells (pMSC) are also routinely isolated, for therapeutic and research purposes. However, our understanding of the diverse phenotypes of placental mesenchymal lineages, and their rela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 86 publications
4
15
0
Order By: Relevance
“…Many studies on SSPCs use plastic adherence, or adherence to fibronectin-coated plates for chondroprogenitors, but numerous studies have shown that the cell surface phenotype of various mesenchymal progenitor populations is altered by attachment, in vitro culture conditions, and passaging (32)(33)(34)(35)(36)(37). Therefore, it is important to identify functionally different SSPCs and define their origins in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on SSPCs use plastic adherence, or adherence to fibronectin-coated plates for chondroprogenitors, but numerous studies have shown that the cell surface phenotype of various mesenchymal progenitor populations is altered by attachment, in vitro culture conditions, and passaging (32)(33)(34)(35)(36)(37). Therefore, it is important to identify functionally different SSPCs and define their origins in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…We used Panel One reported in Boss et al (37) and similar panels used for the analysis of adipose tissue as the backbone of our stain. The panel is shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…FACS is a technique initially developed for immune cell classification, and now is utilized in a variety of fields to identify subpopulation heterogeneity within a larger population [65][66][67] . Traditional approaches utilizing FACS often isolate subpopulations with known markers, making it difficult to identify novel subpopulations utilizing FACS alone.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…Placental villous tissue was carefully dissected away from the foetal membranes and washed thoroughly in PBS to remove maternal blood and debris. Placental explants (∼1 cm 2 ) were largely denuded of trophoblasts (the epithelial cells that are present around the outside of placental villi) by digestion in 10 ml/1 g tissue of Enzyme Digest Solution (1 mg/ml Dispase II (Roche, Mannheim, Germany), 0.5 mg/ml Collagenase A (Roche), and 1.5 mg/ml DNAse l (Sigma-Aldrich, Saint Louis, MO, USA)) in advanced-DMEM/F12 (Gibco, Grand Island, NY, USA) for 10 min at 37 °C as previously described ( Boss et al , 2022 ). Explants were washed repeatedly in PBS and then placed in a 90 mm petri dish and finely macerated with two sterile disposable scalpels (with additional maceration applied to term explants to ensure complete digestion of this more fibrous tissue).…”
Section: Methodsmentioning
confidence: 99%
“…Despite a recent flurry of studies employing single-cell RNA sequencing to investigate placental cell populations ( Suryawanshi et al , 2018 ; Vento-Tormo et al , 2018 ), a method that has revolutionized our understanding of cell heterogeneity, RNA changes are not always representative of protein changes and studies often fail to report on the stromal/endothelial lineages of the placenta ( Liu et al , 2018 ; Vento-Tormo et al , 2018 ; Pique-Regi et al , 2019 ). Recently, we developed a high-dimensional flow cytometry panel to explore the extent of cellular heterogeneity within the first trimester villous core, with a focus on stromal cell populations ( Boss et al , 2022 ). Here, we capitalize on this advance in resolving the placental villous core to better understand how endothelial and perivascular heterogeneity and abundance vary both across gestation and in FGR.…”
Section: Introductionmentioning
confidence: 99%